Analiza porównawcza systemów edukacji krajów Unii Europejskiej i Polski - Grześkowiak, Alicja; Stanimir, Agnieszka (The comparative analysis of educational systems in European Union countries, 2005)
In this paper the educational objectives established by the European Union countries at the meeting in Lisbon in 2000 are presented. The degree of achievement of those targets was evaluated on the basis of some indicators, the countries were classified according to development of educational system. The strengths and the weaknesses of the education in the analyzed countries were pointed out after conducting the correspondence analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 204-219